A Mini Review on Various Skill Illness Types - Ibrahim, Nur Aifiah Binti (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2025)
This paper focuses on a mini review of various self-projected plans and strategies for the future of the skin routine, a healthy route to glowing and rich in vitamins. The reroute of a skin degeneration for the sunken pores in dark spots and uneven skin tone. The delicate and healing effect of the aromatherapy and medicated oil on the glands and bumpy skin adds more smoothened effect for the prolonging of blemished skin. Lyme disease, for example, is prone to the outer environment, and the vectorisation of the breeding sites for the ticks is held. The chances and probabilities to have developing good skin care are to apply more nutrigenomics in line with others to have a substitute in promoting and strategising more skin-oriented products to be more aware of their beauty perspective in terms of health and someone’s well-being over the drop of a liquid for a foamy texture in an easy clean off steps.